First record of phyto-parasitic nematodes associated with potato in Erbil and Duhok Provinces Kurdistan Region, Iraq - Ahmed, Ayoub Ibrahim; Ami, Sulaiman Naif (Journal of Plant Protection Research, 2025)
Potato is considered a crucial food crop globally; however, various biotic factors, including plant-parasitic nematodes, significantly restrict its productivity. This study aimed to identify nematodes associated with potato cultivation in Erbil and Duhok provinces of the Kurdistan Region of Iraq throughout the 2024 growing seasons. Notably, six phyto-parasitic nematodes were recorded for the first time, including: Tylenchorhynchus spp., Ditylenchus destructor, Pratylenchus spp., Paratylenchus spp., Helicotylenchus spp., and Tylenchus spp. The stunt nematode Tylenchorhynchus spp. was the most prevalent nematode in potato producing fields, with a higher population density (241.66 nematodes / 200 g of soil) and maximum percentage of absolute frequency (83.33%), relative frequency (17.41%) and absolute density (171.26%), followed by the pin nematode Paratylenchus, while the lowest percentage of population density (86.33 nematodes / 200 g of soil) was recorded by Tylenchus and minimum percentage of each, absolute frequency (8.33 %) and relative frequency (1.96%) was recorded by the spiral nematode Helicotylenchus. All nematode genera were extracted from infected potato roots and rhizosphere soil while the potato rot nematode Ditylenchus destructor was extracted from infected potato tubers and the surrounding soil. The results indicated that the prevalence and quantity of plant-parasitic nematodes in potato cultivation regions in Erbil and Duhok could potentially lead to significant output losses. Comprehensive surveys are necessary to accurately determine the distribution, frequency, and identification of plant-parasitic nematode species in these regions.